Kinerja Penyuluh Pertanian Berdasarkan Faktor Personal dan Situasional - Syafruddin, -; Hariadi, Sunarru Samsi; Wastutiningsih, Sri Peni (Faculty of Psychology, Universitas Gadjah Mada, 2013)
This study aimed to investigate the influence of personal and situational factors of agricultural extension officers on their performances. The hypothesis assumed that personal factor and situational factor affect the performance of agricultural extension officers. The subjects of this research were 130 agricultural extension officers who were civil servants of Konawe Regency, Southeast Sulawesi Province. To assess the objectivity of these officers’ performances, the research also involved as samples two farmers whom every officer targeted for the extension. Therefore, totally there were 260 farmers participating in the research. The research used a quantitative method with qualitative description. The results of analysis showed that personal factor provided a significant influence on the performances of the officers of agricultural extension as much as 25% at the significance level of α=5%, and the situational factor directly influenced the personal factor as much as 29% at the significance level of α=1%. Keywords: agricultural extension, personal factor, situational factor, performance